PERSUASION STRATEGIES IN THE FRENCH ULTRA-RIGHT DISCOURSE - Hulei , Maryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The paper presents a study of the persuasion strategies in French ultra-right discourse. Persuasion strategies are considered with the aim of researching the construction of the most effective political communication as an instrument of pressure and management of public opinion. The article deals with a linear communication model, which is based on the process of unilaterally transferring information from the speaker to the addressee. This model of information transmission is widespread in the media and aims to directly influence the addressee for the sake of forming persistent beliefs. The theoretical and methodological basis of the research is the work of scientists devoted to the study of general theory of discourse and political discourse. The methodological basis of the work was the techniques and methods of researching political discourse in the framework of a consistent study of its specific features. The author analyzes the discursive strategies and tactics used in the French ultra-right discourse with the aim of influencing the addressee. The essence of speech strategies and rhetoric of the right forces, as well as the range of linguistic means of speech influence and their implementation by these political forces are considered. The main directions of the essential characteristics of persuasion strategies in contemporary French ultra-right discourse are investigated. Ultra-right groups have a large number of supporters in France, whom they attract to their ranks through print and online publications, so consideration of persuasion strategies in French ultra-right discourse to ensure a positive impact on the addressee is available over time. "Ultra-right discourse" refers to the discourse of the ultra-right, often very small groups, whose actions are violent. The term "ultra-right discourse" is intended to differentiate the discourse of radical and "non-parliamentary" groups from the discourse of far-right law-abiding groups. The role of ultra-right discourse in modern French society is revealed, in particular, the manipulative effect of ultra-right political discourse on the addressee is considered. _____________References• Gulej,M. D. «Perekonannja jak osnovna strategija politychnogo dyskursu». Problemy semantyky slova, rechennja ta tekstu 38 (Kyi'v, Logos, 2017).• Dem'yankov, V. Z. «Politicheskiy diskurs kak predmet politologicheskoy filologii». Politicheskaya nauka. Politicheskiy diskurs: istoriya i sovremennye issledovaniya (2002), dostup: http://www.infolex.ru/PolDis.html• Action patriote, accès: www.action-patriote.fr• Guerre de France, accès: http://www.guerredefrance.fr/index.htm• Millière, Guy. La France s’enfonce régulièrement dans le chaos, accès: http://resistancerepublicaine.eu/2019/08/12/guy-milliere-la-france-senfonce-regulierement-dans-le-chaos/• Résistance républicaine, доступ: http://resistancerepublicaine.eu• Sport et islamisme : les liaisons dangereuses, accès: https://rassemblementnational.fr/tribunes-libres/sport-et-islamisme-les-liaisons-dangereuses/